Development of Industrial Oil Crop Crambe abyssinica for Wax Ester Production through Metabolic Engineering and Cross Breeding. (8th April 2019) - Li, Xueyuan; Guan, Rui; Fan, Jing; Zhu, Li-Hua
Abstract: As an important industrial feedstock, wax esters (WEs) have been used as lubricants in a number of technical processes. There is however currently no large-scale biological source for WE production and alteration in metabolic pathways of plant oils for producing WEs could be attractive to the commercial markets. Here, we present the breeding results of long-term studies on successful development of new crambe lines producing WEs through genetic engineering and cross breeding. The transgenic crambe lines producing WEs at over 25% of the total seed oil were first generated by introduction of the jojoba WE biosynthetic genes ScFAR and ScWS . Further improvement of the lines aiming at improving oxidative stability of WEs was achieved through introducing the CaFAD2 -RNAi gene into these lines by crossing. The hybrid lines possessed similar agronomic traits to the wild type and a stable level of WEs over several generations, suggesting a high potential of crambe as an industrial crop for WE production.